Obesity exacerbates influenza-induced respiratory disease via the arachidonic acid-p38 MAPK pathway - Chandrasekaran, Ravishankar; Morris, Carolyn R.; Butzirus, Isabella M.; Mark, Zoe F.; Kumar, Amit; Souza De Lima, Dhemerson; Daphtary, Nirav; Aliyeva, Minara; Poynter, Matthew E.; Anathy, Vikas; Dixon, Anne E. (Frontiers in Pharmacology, 2023)
Obesity is a risk factor for severe influenza, and asthma exacerbations caused by respiratory viral infections. We investigated mechanisms that increase the severity of airway disease related to influenza in obesity using cells derived from obese and lean individuals, and in vitro and in vivo models. Primary human nasal epithelial cells (pHNECs) derived from obese compared with lean individuals developed increased inflammation and injury in response to influenza A virus (IAV). Obese mice infected with influenza developed increased airway inflammation, lung injury and elastance, but had a decreased interferon response, compared with lean mice. Lung arachidonic acid (AA) levels increased in obese mice infected with IAV; arachidonic acid increased inflammatory cytokines and injury markers in response to IAV in human bronchial epithelial (HBE) cells.Obesity in mice, and AA in HBE cells, increased activation of p38 MAPK signaling following IAV infection; inhibiting this pathway attenuated inflammation, injury and tissue elastance responses, and improved survival. In summary, obesity increases disease severity in response to influenza infection through activation of the p38 MAPK pathway in response to altered arachidonic acid signaling.